PENINGKATAN PEMAHAMAN ISI TEKS BERBAHASA INGGRIS MELALUI METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) PADA SISWA KELAS XI IPA 3 SMA JEMBATAN BUDAYA - P.A. Angandari (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2019)
[Title: Improving the Comprehension of English Text Content Through Cooperative Integrated Reading and Composition (CIRC) Method in Grade XI Science 3 Jembatan Budaya Senior High School] Reading is a skill that should be learned also be considered as one of the most important skill because it can affect other skills (listening, speaking, and writing) (Hibbard, 2003). The main purpose of reading is to know the thoughts and ideas expressed in writing (Alderson, 2000).This study also aims to determine the ability of students in understanding English text before and after CIRC method applied in class XI IPA 3 SMA Jembatan Budaya by three aspects of comprehension, those are, the comprehension of text content, lexical cohesion comprehension, grammatical cohesion comprehension. The data source is the 24 students of class XI IPA 3 SMA Jembatan Budaya. Research was held by using classroom action research and consists of three stages; pre-action testing used to determine student’s ability before the test, cycle 1 and cycle 2 to apply CIRC method. Data collection used four instruments; observation, documentation, test and questionnaire. Data analysis which appeared from the research are presented in the form of tables, graphs, and description descriptions.The results showed that CIRC method can improve the reading ability of English of grade 11 IPA 3 SMA Jembatan Budaya. Progress of study is shown by score achievement from pre-test, cycle 1 until cycle 2.